HIV-1 subtype B spread through cross-border clusters in the Balkans: a molecular analysis in view of incidence trends. (1st January 2023) - Jovanovic, Luka; Siljic, Marina; Cirkovic, Valentina; Salemovic, Dubravka; Jevtovic, Djordje; Alexiev, Ivailo; Zidovec-Lepej, Snjezana; Oroz, Maja; Begovac, Josip; Paraskevis, Dimitrios; Skoura, Lemonia; Chaztidimitriou, Dimitrios; et al.
Abstract : Objectives: To analyze phylogenetic relations and assess the role of cross-border clusters in the spread of HIV-1 subtype B across the Balkans, given the general trends of new HIV diagnoses in seven Balkan countries. Design: Retrospective phylogenetic and trend analysis. Methods: In-depth phylogenetic, phylodynamic and phylogeographic analysis performed on 2415 HIV-1 subtype B sequences from 1999 to 2019 using maximal likelihood and Bayesian methods. The joinpoint regression analysis of new HIV diagnoses by country and modes of transmission using 2004–2019 ECDC data. Results: Ninety-three HIV-1 Subtype B transmission clusters (68% of studied sequences) were detected of which four cross-border clusters (11% of studied sequences). Phylodynamic analysis showed activity of cross-border clusters up until the mid-2000s, with a subsequent stationary growth phase. Phylogeography analyses revealed reciprocal spread patterns between Serbia, Slovenia and Montenegro and several introductions to Romania from these countries and Croatia. The joinpoint analysis revealed a reduction in new HIV diagnoses in Romania, Greece and Slovenia, whereas an increase in Serbia, Bulgaria, Croatia and Montenegro, predominantly among MSM. Conclusion: Differing trends of new HIV diagnoses in the Balkans mirror differences in preventive policies implemented in participating countries. Regional spread of HIV within the countries of former Yugoslavia has continued to play an important role even after country break-up, whereas the spread of subtype B through multiple introductions to Romania suggested the changing pattern of travel and migration linked to European integration of Balkan countries in the early 2000s.